Considerações sobre o conceito do vazio na produção artística de Waltercio Caldas e Gordon Matta-Clark - Ramírez Pedraza, Darío Iván (2017)
This thesis aims to bring up a reflection upon the concept of The Void in some of its diverse manifestations in contemporary art, on the basis of the artwork of Waltercio Caldas (Rio de Janeiro, 1946 -) and Gordon Matta-Clark (New York, 1943 – 1978). In b